Left Main Percutaneous Coronary Revascularization - Abdulrahman Almoghairi; Nayef Al-Asiri; Khalid Aljohani; Ayman AlSaleh; Nasser G Alqahtani; Mohammed Alasmary; Rudaynah Alali; Khaled Tamam; Mirvat Alasnag (US Cardiology Review)
Left main (LM) coronary artery disease accounts for approximately 4–6% of all percutaneous coronary interventions (PCIs). There has been mounting evidence indicating the non-inferiority of LM PCI as a revascularization option, particularly for those with a low SYNTAX score. The EXCEL and NOBEL trials have shaped current guidelines. The European Society of Cardiology assigned a class 2a level of evidence B for isolated LM disease involving the shaft and ostium and a class IIb level of evidence B for isolated LM disease involving the bifurcation or additional two- or three-vessel disease and a SYNTAX score <32. However, data on the use of a single stent or an upfront two-stent strategy for distal LM disease are conflicting, wherein the EBC Main trial reported similar outcomes with a stepwise provisional approach and the DKCRUSH-V trial reported better outcomes with an upfront two-stent strategy using the ‘double-kissing’ crush technique. Although several studies have noted better immediate results with image-guided PCI, there are few data on outcomes in LM disease specifically. In fact, the uptake of imaging in the aforementioned landmark trials was only 40%. More importantly, the role of mechanical circulatory support (MCS) has been less well studied in LM PCI. Indiscriminate use of MCS for LM PCI has been noted in clinical practice. Trials evaluating the benefit of MCS in high-risk PCI demonstrated no benefit. This review highlights contemporary trials as they apply to current practice in LM PCI.